BLACK (BRITISH) IDENTITY AND ARCHIVAL RITUALS - Walcott, Rianna (AoIR Selected Papers of Internet Research, 2026)
On April 9th, 2021, just before noon, multiple major news outlets reported the death of Prince Philip, husband to the British monarch Queen Elizabeth II, aged 99. What followed was a subversion of imperial hierarchy – for a time – as Black Briton’s took to Twitter to celebrate the death of a living symbol of oppression. Within 24 hours much of the evidence of this ritual of disrespect was gone: temporarily changed profile pictures had reverted to normal, tweets had been deleted, and the event firmly ensconced in Black British Twitter history. In this paper I frame the ritual archive as Black insurgent practice and an infrastructure of communal memory. Through remixing cultural touchpoints and significant events (Massanari, 2015; Sobande, 2019), Black Britons demarcate ourselves as a public that is adaptively appositional: at once Black, in the ontological sense of belonging to a global community of shared diasporic experience, and British, i.e. physically, temporally, and culturally located within a specific imperial history. Black archival rituals like this run counter to institutional archives (Florini, 2014), rupturing established precedents and prevailing national discourses of identity. In this moment, where control of digital archives is so contingent on institutional power, this kind of counter-institutional archival practice is even more critical, a reminder that collective memory is not contingent on insecure platforms that we contribute to but do not own (Walcott, 2024), but is in fact held in the memory, rituals, and embodied practices of the community’s constituents.